Mapping of pathological manifestations in asphalt pavement through the use of drones - Vasconcelos Fernandes, Rogerio Taygra; Fonseca Cabral, Adriene; Batista Dantas, Gerbeson Carlos; Varela Tinoco, Vinícius Navarro; Azevedo da Silveira, Brenno Dayano; Sousa Junior, Almir Mariano (Revista ALCONPAT, 2021)
This work objective is to study the feasibility of the Drones’ use for mapping and inspecting pathological manifestations in asphalt pavements compared to the traditional method. Sampling plots were established every 20 m, with 6 m extension, making a total of 20 stations, which had their pathological manifestations recorded and calculated with the Global Severity Index for the study area. The results obtained by the reference and alternative methodologies were confronted according to the pathologies identified and the time spent in the surveys. The results showed feasibility in the use of drones for inspection of pathologies in asphalt pavements, based on DNIT 006/2003 - PRO, obtaining results similar to those of the traditional methodology with a significant reduction of the time of operation (33.3%).